Civil liability arising from the breach of contracts by professional sportsmen or the so called “cláusula de rescisión” (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The relationships between sportsmen and their sports clubs are very complex.In the contracts signed between them, it is usual to include clauses in order derepair de damages inflicted to the club, in case of a breach of contract caused bythe sportsmen when they decide to leave their previous club and get hired byanother club of the same sport. I intend to assess those stipulations which quantifiesthe damages causes by a future breach of contract of the sportsmen, and tryto identify is nature. By this study I will conclude that the nature of this type ofclauses is linked to the general rules of the civil Law, more than to the labor Law.
Keywords: sportsmen; professionals; civil liability; punitive clauses